Gender diversity in the UK film music industry - Green, Laura (2020)
This dissertation aims to explore the gender imbalance within the UK film music industry, identify some of the reasons for the imbalance, and recommend directions that future research into the matter should take. Currently, there are substantially fewer female composers than male composers working within the UK film industry. Previous research into the gender diversity of the film industry has primarily focused on the role of the director. This paper focuses on the role of film composer with the intention of broadening the academic fields of both film and music research. Existing studies of the diversity within the film industry have taken a predominantly quantitative approach, providing a great deal of numerical data. This dissertation offers a qualitative approach to provide contextual balance to the numbers. A lack of female role models has been suggested as one reason for the low numbers of females working in film music, this paper provides examples of potential role models by profiling the women that have composed for film in the past, as well as the women working in the field today. Stories are also collected from women new to the industry in order to offer insight into the views of those just beginning their film music composition careers. The participants provide an up-to-date vignette of how the industry works today, what the concerns are of the people working in it, and an insight into whether the hypothesised reasons for a male dominated industry from other research are still relevant in the 2010s and beyond. This dissertation explores the skills and qualities required to excel in film composition and considers if women are inherently disadvantaged in pursuing a film composition career. The counteractive measures from the UK film industry and ‘female-led’ organisations are also examined. It is too early to tell if these are adequate and worthwhile actions for increasing gender diversity within the film music world. Existing narratives surrounding women, their careers, and their abilities are found to be outdated and perpetuating false beliefs that could be deterring women from pursuing a career within film composition. The experiences of those working within the film composition industry portray a different picture to that shown by the statistical data, with many feeling that being female is not a disadvantage when pursuing this career path. Collection of stories relating to women in the UK film music industry prove to be essential in changing the current narrative surrounding gender diversity, and thus affecting measurable change within the statistics. There is vast scope for continued research into this topic, as well as connected disciplines such as sociology, film studies and social policy research.